1986
DOI: 10.1021/jm00157a023
|View full text |Cite
|
Sign up to set email alerts
|

In the search for new anticancer drugs. 17. Linear and cyclic polyether analogs of N,N:N',N':N",N"-tri-1,2-ethanediylphosphoric triamide and N,N:N',N':N",N"-tri-1,2-ethanediylphosphorothioic triamide

Abstract: Linear and cyclic polyether derivatives of N,N:N',N':N'',N''-tri-1, 2-ethanediylphosphoric triamide (TEPA) and N,N:N',N':N'',N''-tri-1,2-ethanediylphosphorothioic triamide (thio-TEPA) are synthesized and evaluated for their antineoplastic activity against the murine lymphocytic leukemia P388. All compounds, except for 7d, were active ranging from 42% to 287% increase in life span (% ILS). All CD2F1 male mice treated with the most active compound (7a) at 90 mg/kg per day for 9 days were alive after 30 days, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These facts can be explained , by assuming that the nitroxyl radical is a carrier group which facilitates the transport of the drug through the biological membranes to the cellular DNA. In support of this hypothesis it was found that neutral or weakly acidic or basic nitroxyls rapidly permeate through cell membrane and that a plausible correlation of the anticancer activity of spin-labeled compounds with their lipophilic properties can be established. ,
23 Structures for Section VII.G
…”
Section: G Nitroxyl (Aminoxyl) Analogsmentioning
confidence: 91%
See 1 more Smart Citation
“…These facts can be explained , by assuming that the nitroxyl radical is a carrier group which facilitates the transport of the drug through the biological membranes to the cellular DNA. In support of this hypothesis it was found that neutral or weakly acidic or basic nitroxyls rapidly permeate through cell membrane and that a plausible correlation of the anticancer activity of spin-labeled compounds with their lipophilic properties can be established. ,
23 Structures for Section VII.G
…”
Section: G Nitroxyl (Aminoxyl) Analogsmentioning
confidence: 91%
“…In support of this hypothesis it was found 578 that neutral or weakly acidic or basic nitroxyls rapidly permeate through cell membrane and that a plausible correlation of the anticancer activity of spin-labeled compounds with their lipophilic properties can be established. 579,580 Previous research revealed 104,581 that BCNU (33), CCNU (137b), and MeCCNU (138b) rapidly enter the cerebrospinal fluid and, thus, can be used to control meningeal tumors. Further, the nitroxyl radicals are known 582 to cross the blood-brain barrier at the site of the diseased tissue.…”
Section: G Nitroxyl (Aminoxyl) Analogsmentioning
confidence: 99%
“…In support of this hypothesis, it was foun d th at neutral or w eakly acidic o r basic nitroxyls are [3 3 ] rapidly perm eatin g through cell m em branes, and th a t a plausible correlatio n of the antineoplastic activity of com pounds 2, 3 and analogs w ith th eir lipophilic p ro p ertie s can be established [34,35], It is know n th a t B C N U (lb), C C N U (lc) and M eC C N U (ld) rapidly e n te r the cerebrospinal fluid and thus can be used to control the m eningeal tum ors [36,37], F u rth e r, the nitroxyl radicals are know n to cross the blood brain b arrier [38] at the site o f the diseased tissue. H en ce, we assum ed th a t a com b in a tion of the ch lo ro eth y ln itro so u rea and the nitroxyl m oiety could lead to a m ore viable drug w hich could be follow ed pharm acokinetically by E S R in anim al m odels, and diagnostically during th erap y by N M R im aging [39].…”
Section: Introductionmentioning
confidence: 99%